A Comprehensive Analysis of Graduated Residents’ and Faculty Members’ Attitudes on Iranian Radiation Oncology Board Examination: A Cross-sectional Study - Ameri, Ahmad; Soleiman, Ahmady; Heidarzadeh, Abtin; Ainaz, Ainaz; Akbarilakeh, Maryam (Reports of Radiotherapy and Oncology, 2021)
Background: The Iranian radiation oncology board examination (IROBE) includes a multiple-choice question (MCQ) examination and an objective structured clinical examination (OSCE). The current mission of IROBE is to qualify the graduated residents (GRs) in terms of clinical competence. However, lack of active monitoring of its construction and administration can impair the evaluation of GR competencies. Objectives: To determine the strengths and limitations of IROBE. Methods: This cross-sectional online survey involved faculty members (FMs) and GRs as constructors and participants of the IROBE, respectively. The target time window for inclusion in the study was set between 2015 and 2019. To evaluate the strengths and limitations of IROBE, a 22-item questionnaire was distributed among FMs and a 29-item questionnaire among GRs. The Mann-Whitney U test and Pearson's chi-square test were applied to find the association between the ordinal and nominal variables, respectively. Results: The surveys were sent to 35 FMs and 107 GRs. A total of 16 (45%) FMs and 42 (39%) GRs completed the survey. Overall, the majority of FMs and GRs stated that IROBE has average to poor quality in evaluating all aspects of clinical abilities (62.5 vs. 76.1% in clinical competence, P = 0.07; 62.5 vs. 71.4% in clinical knowledge, P = 0.19; 100 vs. 92.9% in medical ethics, P = 0.21; and 93.7 vs. 95.3% in responsibility, P = 0.15). However, FMs assigned a higher score to OSCE in the assessment of clinical performance compared to GRs (P = 0.02). Most FMs and GRs declared that IROBE requires extreme to high improvement in both MCQ and OSCE components (75 vs. 59.52% and 87.5 vs. 90.47%, respectively). Conclusions: According to the participants, the present structure of IROBE has several drawbacks in both MCQ and OSCE components. Considering the highlighted strengths and limitations can help the IROBE constructors to improve its quality.